Development, Validation, and Application of School Audit Tool (SAT): An Effective Instrument for Assessing Traffic Safety and Operation Around Schools - Khaled Shaaban (6393764) (2019)
There is a need for a reliable school audit tool with well-defined scales to convert qualitative evaluation of existing school sites into a quantitative assessment in order to help public agencies to improve schools’ safety and efficiency. In this study, a new, simple, and versatile School Audit Tool (SAT) was developed and tested. SAT was formed using a 30-item checklist categorized into four domains: school site assessment, road network assessment, parking/loading assessment, and active transport assessment. The tool was applied on a sample of 22 schools. Then, categorical and item-by-item Intraclass Correlation Coefficients (ICC) were calculated to validate the tool. The results showed acceptable overall test-retest (ICC = 0.919) and inter-rater reliability (ICC = 0.843) across all items and domains. SAT’s adaptable framework to assess and compare the safety and efficiency of schools is reliable, easy-to-use, and comprehensive. The tool is also effective in ranking schools and identifying items that may require upgrades or modifications. Other Information Published in: Sustainability License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.3390/su11226438